Endovascular First Approach for Embolic Acute Mesenteric Ischaemia: a 15 Year Single Centre Retrospective Study - Bakó, Eszter; Erik, Palm; Pengermä, Pasi; Karjalainen, Jari; Halonen, Jari; Manninen, Hannu; Saari, Petri; Kärkkäinen, Jussi M. (Elsevier, 2026)
Objective
To evaluate outcomes of endovascular treatment as the first line approach for acute mesenteric ischaemia (AMI) caused by embolic occlusion of the mesenteric arteries.
Methods
This retrospective, single centre study included consecutive patients with occlusive AMI between 2009 and 2024. Patients with acute embolic occlusion of the mesenteric artery were included, whereas patients with thrombotic AMI were excluded. The diagnosis was confirmed by computed tomography, intra-operative findings, or autopsy. Main outcomes included rates of technical success, endovascular procedure related complications, 30 day mortality, laparotomy, and bowel resection.
Results
Of 63 patients with embolic AMI (mean age 79 ± 12 years), 15 were treated without attempted revascularisation, of whom three survived. Forty eight patients (76%, mean age 79 ± 11 years) underwent endovascular revascularisation as the first line treatment, with technical success in 47 (98%). Mechanical aspiration was performed in 45 patients, with additional balloon angioplasty in four, stenting in nine, thrombolysis in three, and stent retriever thrombectomy in three. Plain stent placement without aspiration was performed in three patients. Laparotomy was performed in 15 patients (35%) undergoing endovascular treatment; six had clinical signs of peritonitis (13%) and nine (21%) required bowel resection. Seven patients (15%) had endovascular procedure related complications (superior mesenteric artery dissection in five, access site bleeding in one, and access site pseudoaneurysm in another patient). Of the 48 patients treated with endovascular revascularisation, 21 (44%) died within 30 days. Factors prominently associated with early death after endovascular revascularisation in univariable analysis were older age (p = .001), clinical signs of peritonitis (p = .003), decreased bowel wall enhancement (p = .004), increased lactate level (p = .006), low bicarbonate level (p = .008), and low base excess (p = .009).
Conclusions
An endovascular first approach was suitable for most patients, with a good technical success rate and acceptable mortality rate considering the high mean age of the non-selected patients with AMI. One third underwent laparotomy after endovascular treatment, whereas all patients would have required laparotomy if treated with open embolectomy.